Kagurabachi. 01 - Hokazono, Takeru (Shonen Jump manga., 2024)
"As a young boy, Chihiro trains every day under his father to become a swordsmith. Although different in temperament, the two spend peaceful days laughing and working together. But one day, tragedy strikes... Now Chihiro burns with hatred and sets out to exact revenge. Following clues left behind by a ruthless yakuza organization, Chihiro confronts the Hishaku, a deadly group of sorcerers that may be behind his father's murder!"--